2009
DOI: 10.1158/1078-0432.ccr-08-1355
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Growth-Suppressive MicroRNAs in Lung Cancer

Abstract: Purpose MicroRNA (miRNA) expression profiles improve classification, diagnosis, and prognostic information of malignancies, including lung cancer. This study uncovered unique growthsuppressive miRNAs in lung cancer. Experimental Design miRNA arrays were done on normal lung tissues and adenocarcinomas from wild-type and proteasome degradation-resistant cyclin E transgenic mice to reveal repressed miRNAs in lung cancer. Real-time and semiquantitative reverse transcription-PCR as well as in situ hybridization a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
161
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(170 citation statements)
references
References 29 publications
8
161
0
1
Order By: Relevance
“…In the present study, the expression levels of hsa-miR-34-c, hsa-miR-126 and hsa-miR-145 were downregulated, while the expression levels of hsa-miR-183 was upregulated (Table II). The targets of hsa-miR-34, cyclin E and p53, are associated with the cell cycle and tumor formation (26,27); the low expression of hsa-miR-34 may result in upregulation of cyclin E and p53, which is crucial in the development of SCLC. The epidermal growth factor receptor (EGFR) encoded by the target of hsa-miR-145 may inhibit cancer growth (28); the downregulation of hsa-miR-145 in SCLC may generate an increase in the expression levels of EGFR and thus promote cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the expression levels of hsa-miR-34-c, hsa-miR-126 and hsa-miR-145 were downregulated, while the expression levels of hsa-miR-183 was upregulated (Table II). The targets of hsa-miR-34, cyclin E and p53, are associated with the cell cycle and tumor formation (26,27); the low expression of hsa-miR-34 may result in upregulation of cyclin E and p53, which is crucial in the development of SCLC. The epidermal growth factor receptor (EGFR) encoded by the target of hsa-miR-145 may inhibit cancer growth (28); the downregulation of hsa-miR-145 in SCLC may generate an increase in the expression levels of EGFR and thus promote cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that miR-143 and miR-145 expression levels are downregulated in rodent lungs exposed to cigarette smoke (which is a severe carcinogen) [46]. Additional studies have shown Brought to you by | MIT Libraries Authenticated Download Date | 5/9/18 9:15 AM that miR-143 and miR-145 have an inhibitory effect on lung cancer cell growth in both mice and humans [47]. This regulation progress involves many target genes, such as C-MYC, NUDT1, EGFR and OCT4 [48].…”
Section: Tumor Suppressive Mirnas In Lung Cancermentioning
confidence: 99%
“…Accordingly, when a miRNA is identified as a candidate for tumor suppression or oncogenesis, its function will be confirmed by gain/loss studies of miRNA in the established model [65]. Then, when a specific miRNA is found to play an important role in lung cancer development, specific targeting to reduce lung carcinogenesis within the same species will be attempted.…”
Section: Future Directions Of Mirnas Of Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective studies, cyclin E level has been the best predictor of survival comparing with canonical clinical factors (age, tumor size, nodal status, stage of disease) and biologic markers (steroids and Her-2 receptor status, ploidy, proliferation index, cyclins D1 and D3) (Keyomarsi et al, 2002;Liu et al, 2013). The known mechanisms of these elevated and constitutive expressions include cyclin E gene amplification, overexpression of its mRNA, increased expression of its protein, tumor specific proteolytic cleavage of the full length protein and altered profiles of microRNAs expression (Keyomarsi and Pardee, 1993;Porter et al, 2001;Ekholm-Reed et al, 2004;le Sage et al, 2007;Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%